2010
DOI: 10.1007/s00024-010-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Energy and Displacement Demands for Performance-Based Seismic Engineering

Abstract: Artículo de publicación ISIThe development of a scientific framework for performance-based seismic engineering requires, among other steps, the evaluation of ground motion intensity measures at a site and the characterization of their relationship with suitable engineering demand parameters (EDPs) which describe the performance of a structure. In order to be able to predict the damage resulting from earthquake ground motions in a structural system, it is first necessary to properly identify ground motion param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The objective of these proposals is not only to improve the predictive efficiency of the IM for all damage levels of a given structure, but also to account for the IM computability through a ground-motion hazard analysis without the need of any new attenuation relationships. Moreover, numerous spectrum-based scalar IMs including energyderived ones were investigated, and studies showed that velocity-based IMs are in general better correlated to deformation demands especially in the case of medium rise frame structures (Akkar and Ö zen 2005;Riddell 2007;Yakut and Yilmaz 2008;Jayaram et al 2010;Mollaioli et al 2011). In Jayaram et al (2010) and Mollaioli et al (2011), the effect of near-fault ground motions and different soil types was also taken into account in evaluating predictive capabilities of the prescribed IMs.…”
Section: Introductionmentioning
confidence: 98%
“…The objective of these proposals is not only to improve the predictive efficiency of the IM for all damage levels of a given structure, but also to account for the IM computability through a ground-motion hazard analysis without the need of any new attenuation relationships. Moreover, numerous spectrum-based scalar IMs including energyderived ones were investigated, and studies showed that velocity-based IMs are in general better correlated to deformation demands especially in the case of medium rise frame structures (Akkar and Ö zen 2005;Riddell 2007;Yakut and Yilmaz 2008;Jayaram et al 2010;Mollaioli et al 2011). In Jayaram et al (2010) and Mollaioli et al (2011), the effect of near-fault ground motions and different soil types was also taken into account in evaluating predictive capabilities of the prescribed IMs.…”
Section: Introductionmentioning
confidence: 98%
“…Energy parameters, as cumulative measures, have been demonstrated to be strongly related to EDPs in seismic hazard analysis because it considers the amplitude, frequency, and duration of ground motion. 26,27 For example, structure-specific energy parameters, such as absolute input energy, 28 the total dissipated energy, 29 and referential energy, 30 are confirmed as useful indices in predicting the structural behavior. 31 The non-structure-specific energy parameters related to ground motion amplitude (such as 𝐼 𝑎 , CAV, and 𝑎 𝑟𝑚𝑠 ) and response spectrum (such as ASI and SI ) are also widely used as IMs in seismic hazard and risk analysis.…”
Section: 𝑇 𝑔mentioning
confidence: 99%
“…Although traditional methodologies for earthquake-resistant design do not consider cumulative plastic deformation demands, there is strong evidence that, under certain circumstances, the maximum displacement response may not be a good indicator of structural damage. In the presence of large cumulative plastic deformation demands, long-duration ground motions can lead to failure of structural elements at deformation levels that are significantly lower than those established for monotonic loading (Arroyo and Ordaz, 2007; Bojórquez et al, 2009; Cheng et al, 2015; Cosenza and Manfredi, 1996; Fajfar, 1992; Kalkan and Kunnath, 2008; Kunnath and Chai, 2004; Leelataviwat et al, 2009; Mollaioli et al, 2011; Teran-Gilmore and Jirsa, 2005; Trifunac, 2008). This type of failure, usually addressed as low-cycle fatigue, requires a careful assessment of the dissipated plastic energy.…”
Section: Relationship Between Dissipated Plastic Energy and Maximum Displacementmentioning
confidence: 99%